Evaluating Government Revenue Through Property Taxation in Nigeria - Egbe, C. (International Journal of Real Estate, 2025)
Property taxation is a durable and under-utilized source of government revenue in many developing countries. This paper evaluates the contribution of property taxation to government revenue, examines institutional and administrative obstacles to effective implementation, and proposes strategies for reform suitable for the Nigerian context. Using a conceptual and evaluative approach based on secondary data (academic literature, international reports, and national policy documents), the paper highlights contrasts between jurisdictions that have successfully mobilized property tax revenue (e.g., Lagos State, Kenya, South Africa, United Kingdom) and contexts where the potential remains unrealized. Key findings indicate that digitization of cadastral records, regular revaluation, legal harmonization, capacity building, and transparent use of proceeds are central to improving yield and compliance. The study concludes with policy recommendations for Nigerian subnational governments to strengthen internally generated revenue through property-based taxation.